From darkness to light: children speak of divine encounter. Issue 1 (2nd January 2017) - Lovelock, Pauline; Adams, Kate
Abstract: Studies have shown that children share both positive and dark spiritual experiences. The former dominates the literature but whilst the need to address the dark side of spirituality has been raised it has not, as yet, been dealt with as widely as the more positive aspects. This paper draws on an empirical study with 44 children aged 8–11 who were interviewed in school after visiting a sacred space. Three key themes arising from their conversations are covered in this paper: divine encounter; physical feelings and fear. It is argued that the most appropriate way of understanding these phenomena is to draw on different fields and disciplines, notably although not exclusively, theology, psychoanalysis, psychology and neuroscience. The paper concludes that it is important to recognise both the light and dark and the blurred boundaries between them, in addition to different ways of perceiving them, in order to understand the whole child.